Environmental stimulation in Huntington disease patients and animal models - Novati, Arianna; Nguyen, Huu Phuc; Schulze-Hentrich, Julia (Neurobiology of disease, 2022)
While Huntington disease (HD) is caused solely by a polyglutamine expansion in the huntingtin gene, environmental factors can influence HD onset and progression. Here, we review studies linking environment and HD in both humans and animal models. In HD patients, we find that: (i) an active lifestyle associates with both a delayed age at onset of HD and a decreased severity of symptoms, (ii) applying physical exercise and behavioral therapies in small cohorts of HD subjects indicate promising effects on the HD symptomatology, (iii) Mediterranean diet correlates with lower motor impairment, and treatments based on omega-3 fatty acids improve motor function , whereas (iv) increased cortisol levels associate with specific HD symptoms. In animal models, in line with the evidence in humans, physical exercise, environmental enrichment and different types of dietary intervention ameliorate or delay several HD phenotypes. In contrast, stress appears to be involved in the HD pathogenesis, and HD mice present increased stress sensitivity. Importantly, studies in animal models have uncovered several molecular factors mediating environmental effects on HD associated neuropathology. However, the influence of the environment on several key HD mechanisms as well as the underlying regulatory factors remain to be explored. Given the role of epigenetic factors and modifications in the interplay between environment and genes, the exploration of their role as mechanisms underlying the environmental action in HD is a promising avenue for both our fundamental understanding of the disease and as a potential for therapy. •Environmental stimulation modulates Huntington disease (HD) onset and progression.•Environmental stimulation in HD rodents affects pathology and neuroplasticity.•The regulatory factors mediating environmental effects in HD are unknown.•Epigenetic factors are key promising mediators of the environmental action in HD.•HD preclinical studies should combine environmental stimulation and other therapies.